Recycling Hydrocarbon Cuts into FCC Units - Fernandez, M. L. (2002)
A bench scale reactor, which is a simulator of FCC riser units, has been used to study the upgrading of low value hydrocarbon cuts (a heavy coker naphtha and a visbreaker naphtha) by catalytic cracking of a mixture of these cuts (20 wt %) with the conventional feedstock (vacuum gas oil). The results of yield and composition of gasoline have been compared with those obtained by catalytic cracking of vacuum gas oil and with those obtained following other upgrading strategies for these cuts, such as their direct catalytic cracking or their blending with the gasoline stream of the FCCU. In general terms, increases in gasoline yields oppose to losses of its quality. The results show that the cracking of the heavy paraffins contained in these naphthas is inhibited by the adsorption of heavy olefins present in these cuts. Coke yields are not higher than the ones obtained when cracking standard VGO, and then the impact on units' heat balances would be negligible.